The Southern African Development Community (SADC) intervention in the Lesotho conflict in 1998 - Mukwevho, Shavhani Abraham (Department of Political Studies, 2021)
What role does regional organisation play when peace and security is at stake in the region? Although several literatures on the Lesotho conflict of 1998 have been written, the intervention by Southern African Development Community does not answer the question if the intervention was carried out in compliance with the SADC Treaty and Protocols on Peace and Security. The effectiveness of a regional organisation in resolving conflicts, strengthens regionalism and create environment conducive for economic growth and political stability. While the Lesotho conflict in 1998 was resolved through the use of armed forces, it posed challenges for an empirical approach, in that regard the qualitative approach was followed to obtain information from the existing literature, journals and magazines on the conflict resolution and management. The Lesotho conflict of 1998 serves as a good case study to illustrate the role of SADC on peace and security and the impact on regional integration. In order to comprehend and make efficient analysis of the impact of the SADC interventions in the Lesotho conflict 1998, the theories and approaches that define the characteristics of actors and behavioural patterns leading to the integration while some might provide strategies for conflict resolution were considered. The discussion on normative and institutional framework of SADC on peace and security, serves as a platform to analyse the SADC's Organ on Politics, Defence, Security and Cooperation. The study further analyses the nature and the root causes of conflict and the role players such as the military forces from member states in conflict resolution and management. The study concludes that SADC's intervention in Lesotho conflict 1998 was without full mandate of member states as the decision was not recommended from the cluster Ministerial Committee to be approved by the Summit or the Organ on Troika. The armed forces that intervened were from South Africa and Botswana whose interest did not represent the region as whole. However, it is argued that when the state's peace and security is at stake, the choices are limited and therefore it could be justified to take any action to resolve the conflict without necessarily following all the procedures, and that simply justify the intervention by the South Africa National Defence Force in resolving the Lesotho conflict in 1998.